Professional Versus Self-Applied Makeup: Do Makeup Artists Add Value?. (August 2021) - Batres, Carlota; Porcheron, Aurélie; Courrèges, Sandra; Russell, Richard
While a number of studies have investigated the effects of makeup on how people are perceived, the vast majority have used professionally applied makeup. Here, we tested the hypothesis that professional makeup is more effective than self-applied makeup. We photographed the same target women under controlled conditions wearing no makeup, makeup they applied themselves, and makeup applied by professional makeup artists. Participants rated the faces as appearing more attractive, more feminine, and as having higher status when wearing professional makeup than self-applied makeup. Secondarily, we found that participants perceived the professional makeup as appearing heavier and less natural looking than the self-applied makeup. This work shows that professional makeup is more effective than self-applied makeup and begins to elucidate the nature of makeup artistry. We discuss these findings with respect to personal decoration and physical attractiveness, as well as the notion of artists as experts.